2020
DOI: 10.1002/aenm.201903854
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Trifunctional Electrocatalysts Based on FeCo/Co2P Hybrid Nanoparticles for Zinc–Air Battery and Self‐Powered Overall Water Splitting

Abstract: Currently, it is still a significant challenge to simultaneously boost various reactions by one electrocatalyst with high activity, excellent durability, as well as low cost. Herein, hybrid trifunctional electrocatalysts are explored via a facile one‐pot strategy toward an efficient oxygen reduction reaction (ORR), oxygen evolution reaction (OER), and hydrogen evolution reaction (HER). The catalysts are rationally designed to be composed by FeCo nanoparticles encapsuled in graphitic carbon films, Co2P nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
162
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(177 citation statements)
references
References 41 publications
5
162
1
Order By: Relevance
“…The performance for the NiCo–CeO 2 ||NiCo(OH) x –CeO 2 electrolyzer also outperforms most recently reported electrolyzers based on non‐noble bifunctional electrocatalysts (Figure 5e; Table S4, Supporting Information). [ 45–59 ]…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The performance for the NiCo–CeO 2 ||NiCo(OH) x –CeO 2 electrolyzer also outperforms most recently reported electrolyzers based on non‐noble bifunctional electrocatalysts (Figure 5e; Table S4, Supporting Information). [ 45–59 ]…”
Section: Resultsmentioning
confidence: 69%
“…The performance for the NiCo-CeO 2 ||NiCo(OH) x -CeO 2 electrolyzer also outperforms most recently reported electrolyzers based on non-noble bifunctional electrocatalysts (Figure 5e; Table S4, Supporting Information). [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] The excellent overall water splitting activity of the NiCo-CeO 2 ||NiCo(OH) x -CeO 2 electrolyzer is not only attributed to the high intrinsic catalytic activities of NiCo-CeO 2 / GP and NiCo(OH) x -CeO 2 /GP, but also to the self-supported electrode structure. Due to the in situ growth of active species on conductive substrate, the interface resistances of the self-supported NiCo-CeO 2 /GP and NiCo(OH) x -CeO 2 /GP electrodes are greatly lower than those of the Pt/C(20%)/GP and RuO 2 /GP electrodes by physically coating (Figure S25, Supporting Information), which are conducive to the rapid electron transfer.…”
Section: Resultsmentioning
confidence: 99%
“…XPS results of Figure 5E show that the binding energy of Co does not change much, which indicates that Co 3 O 4 does not take part in electrochemical reactions. Based on the above analysis, the working mechanism of our cathode can be summarized in Figure 5F (Cheng et al, 2016 ; Shi et al, 2020 ). Many studies have also found that Mn 3 O 4 has a tendency of phase transition to a layered MnO 2 in the cycling process (Jabeen et al, 2017 ; Hao et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding compounds are also expensive. In particular, their relatively lower stability in alkaline electrolytes also limits their wide application [10–14] …”
Section: Introductionmentioning
confidence: 99%
“…In particular, their relatively lower stability in alkaline electrolytes also limits their wide application. [10][11][12][13][14] Fe-, Ni-, and Co-based compounds are considered to be the most promising candidates for OER catalysts due to their excellent catalytic performance and low cost. [15][16][17][18][19][20][21] In recent years, there are many studies about these low-cost catalysts.…”
Section: Introductionmentioning
confidence: 99%